The Impact Analysis of Raw Material Price on Firm Survival - Sry Rahayu Febriani (Signifikan: Jurnal Ilmu Ekonomi, 2016)
This research examines the effect of input price changes on firm survival. The increasing on import activities in the last decades indicates that manufacturing industry depends on imported raw material. It leads the industry extremely vulnerable to the global economic shocks. Some of the industries that depend on imported raw material is unlikely to survive in the crisis. Using firm level data from the Annual Survey of Manufacturers for the period 2008-2012 and probit estimation with price data of input as main variables, we find that change of input price significantly decreasing the probability of firm survival. Firm size and age as the main determinant of survival consistent with previous studies. DOI: 10.15408/sjie.v5i2.3236